2016
DOI: 10.1016/j.cell.2015.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Human DROSHA

Abstract: MicroRNA maturation is initiated by RNase III DROSHA that cleaves the stem loop of primary microRNA. DROSHA functions together with its cofactor DGCR8 in a heterotrimeric complex known as Microprocessor. Here, we report the X-ray structure of DROSHA in complex with the C-terminal helix of DGCR8. We find that DROSHA contains two DGCR8-binding sites, one on each RNase III domain (RIIID), which mediate the assembly of Microprocessor. The overall structure of DROSHA is surprisingly similar to that of Dicer despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
238
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(249 citation statements)
references
References 47 publications
(86 reference statements)
7
238
1
1
Order By: Relevance
“…A crystal structure of human Drosha bound to the C-terminal helix of DGCR8 was recently solved; this structure was used to build a model for how Drosha might interact with the primiRNA substrate and a pair of DGCR8 dimers. This hypothetical model of the Microprocessor complex implies that the Rhed region of DGCR8 dimers binds the apical stemloop junction of the pri-miRNA, with the DGCR8 dimers oriented in an asymmetrical fashion [13]. This model is reinforced by biochemical studies, which clearly implicate selective DGCR8 binding to the apical stem-loop junction in a ratio of 2:1:1 (DGCR8 dimer:Drosha:pri-miRNA substrate) [12].…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…A crystal structure of human Drosha bound to the C-terminal helix of DGCR8 was recently solved; this structure was used to build a model for how Drosha might interact with the primiRNA substrate and a pair of DGCR8 dimers. This hypothetical model of the Microprocessor complex implies that the Rhed region of DGCR8 dimers binds the apical stemloop junction of the pri-miRNA, with the DGCR8 dimers oriented in an asymmetrical fashion [13]. This model is reinforced by biochemical studies, which clearly implicate selective DGCR8 binding to the apical stem-loop junction in a ratio of 2:1:1 (DGCR8 dimer:Drosha:pri-miRNA substrate) [12].…”
Section: Discussionmentioning
confidence: 57%
“…Each sample tube was sealed with a septum and the headspace purged with N 2 (g), in the case of Fe(II)- 13 CO Rhed samples, or CO(g) in the case of natural abundance Fe(II)-CO Rhed samples. Fe(II)- 13 CO Rhed samples were prepared by anaerobic transfer of 4 mL of 13 CO to the protein sample tube via gas-tight syringe. The samples were heated to 44 °C and sodium dithionite solution was added to a final concentration of 8 mM.…”
Section: Resonance Raman Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, RNAP II generates capped primary miRNA (pri-miRNA) transcripts [50,51] , which are trimmed in the nucleus by the Microprocessor complex consisting of the RNase III DROSHA and the RNA binding DiGeorge syndrome chromosomal region 8 (DGCR8) protein [52,53] . ARS2 interacts with DROSHA and is required for the stability and efficient processing of pri-miRNA to precursor miRNA (pre-miRNA) by the Microprocessor [8] .…”
Section: Ars2/serrate and Microrna Biogenesismentioning
confidence: 99%
“…Although DROSHA was only discovered over a decade ago [9], it was recently that Kwon et al [10] have reported the 3.2 Å crystal structure of a DROSHA construct (aa 390-1 365) in complex with the C-terminal helix (aa 728-750) of DGCR8 ( Figure 1C). The overall structure adopts an elongated shape with the two RIIIDs located on one side and the N-terminal segment of the CED domain located on the other side.…”
mentioning
confidence: 99%